Neuroanatomía Funcional - Afifi, Adel K.; Bergman, Ronald A. (McGraw-Hill's AccessMedicina., 2020)
This new edition went through a comprehensive review and update process. Terms were replaced to accommodate what is most widely used in the fields of neurology, neuropsychology, and neurosurgery. Within the novel scientific concepts, an update was carried out to keep up with the current state of knowledge. In addition, a chapter on the peripheral nervous system was added, since this topic is included in most neuroanatomy courses and is not addressed in the bulk of the titles on this discipline. Finally, the design of the book was updated to facilitate its reading, changing the typography, optimizing the spaces and increasing the size of the images.